2015
DOI: 10.1016/j.cmet.2015.08.018
|View full text |Cite
|
Sign up to set email alerts
|

MSC Transplantation Improves Osteopenia via Epigenetic Regulation of Notch Signaling in Lupus

Abstract: SUMMARY Mesenchymal stem cell transplantation (MSCT) has been used to treat human diseases, but the detailed mechanisms underlying its success are not fully understood. Here we show that MSCT rescues bone marrow MSC (BMMSC) function and ameliorates osteopenia in Fas-deficient-MRL/lpr mice. Mechanistically, we show that Fas deficiency causes failure of miR-29b release, thereby elevating intracellular miR-29b levels, and downregulates DNA methyltransferase 1 (Dnmt1) expression in MRL/lpr BMMSCs. This results in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

9
241
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 217 publications
(252 citation statements)
references
References 52 publications
9
241
0
2
Order By: Relevance
“…They can transmit a variety of signaling molecules, including nucleic acids mainly mRNA and microRNA, functional proteins, and lipids 12. Owing to the small size of exosomes, they can escape from the rapid phagocytosis by mononuclear phagocytes, steadily carry and deliver drugs in circulation, and pass through vascular endothelium to target cells 13.…”
Section: Introductionmentioning
confidence: 99%
“…They can transmit a variety of signaling molecules, including nucleic acids mainly mRNA and microRNA, functional proteins, and lipids 12. Owing to the small size of exosomes, they can escape from the rapid phagocytosis by mononuclear phagocytes, steadily carry and deliver drugs in circulation, and pass through vascular endothelium to target cells 13.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Liu et al [13] showed that allogeneic MSCT could rescue autologous bone marrow MSCs function and ameliorate osteopenia in Fas-deficient-MRL/lpr mice, which could change the epigenetic cascade in vivo. So the long-term safety of MSCT in human must be emphasized and investigated.…”
Section: Introductionmentioning
confidence: 99%
“…suggested by Liu et al (2015). Potentially, wild-type MSC-EVs could also transfer mRNA, miRNA, cytosolic proteins, and other membrane proteins to elicit and/or potentiate the observed epigenetic changes.…”
mentioning
confidence: 99%
“…Meanwhile, although Liu et al (2015) did not investigate if secretory factors other than EVs could supplement Fas function, it is difficult to imagine how cytokines and small molecules can upregulate Fas in cells that lack a functional Fas gene. A complex interplay of signaling factors is typically necessary to elicit epigenetic changes (Mohammad and Baylin, 2010).…”
mentioning
confidence: 99%